(untitled) (Fiep Bulletin - online, 2014)
The present study had as goal to evaluate the impact of 12 weeks of weight training circuit on body composition indicators. Six sedentary girls pospubescent but apparently healthy at Transpiração Fitness Center in Caçador - SC, were chosen for the study. The circuit training occurred during 12 weeks (2 sections a week in two alternated days). Ten exercises composed the circuit training program, each one was realized in 3 series of 12 maximum repetitions (70% of 1 RM) and with an interval of recuperation being, the change from one exercise to another exercise. Skinfolds measures were collected before and after the period of intervention. The results through the Student test "t" compared revealed significant statistically difference on the percentual of fat (-11,01%), on the fat mass (-9,41%) and an increase on the lean mass (+4,72%) from the pre-period training to the post-period training (p<0,05). On the whole body mass there was an increase of 1,72%, not occurring significant statistical differences (p>0,05). The results suggest that the weight training circuit have significant answers on the percentual of fat, fat mass and lean mass in pospubescent girls, however only the circuit training seems to be insufficient for the loss of the whole body mass on female teenagers. Researches with more duration and samples must be done to observe the results of the circuit training on the whole body mass, indicating if the circuit training can keep or control the body weight.